DOI: 10.24834/isbn.9789178770779
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoints about Educational Language Policies: Multilingualism in Sweden and Switzerland

Abstract: This thesis is based on three international peer-reviewed publications and one submitted manuscript under review. The articles are appended to the thesis and will be referred to by the roman numerals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 204 publications
0
2
0
Order By: Relevance
“…31-48) that 'multilingualism should be centrally linked with shared communication, economic and civic betterment, and social cohesion. However, (Lundberg, 2020) assumes that if a political entity of a country, like Switzerland, is multilingual, then the population is also multilingual. Lundberg (2019) stated that multilingualism, capabilities in the registers of different linguistic codes, is a critical element of the Swiss national culture.…”
Section: Language Culture In Switzerlandmentioning
confidence: 99%
“…31-48) that 'multilingualism should be centrally linked with shared communication, economic and civic betterment, and social cohesion. However, (Lundberg, 2020) assumes that if a political entity of a country, like Switzerland, is multilingual, then the population is also multilingual. Lundberg (2019) stated that multilingualism, capabilities in the registers of different linguistic codes, is a critical element of the Swiss national culture.…”
Section: Language Culture In Switzerlandmentioning
confidence: 99%
“…Notwithstanding a few exceptions (e.g., Lundberg, 2020), comparisons with other countries in Scandinavia and the European mainland are few and far between. Swedish educational sciences have at times suffered critique for not being sufficiently international, and the question is whether the lack of comparative studies observed contributes to this critique.…”
Section: Desirable Topics For Future Researchmentioning
confidence: 99%